Butler matrix using circular and mitered bends at 2.4 GHz - Mariadoss, P. Q.; Rahim, M. K. A.; Abd. Aziz, M. Z. A. (2005)
This paper presents two designs of a four-port Butler matrix to feed a switched beam antenna array for Wireless Local Area Network (WLAN) at 2.4 GHz. The two methods applied in designing a beamforming network based on the Butler matrix are the circular and mitered bends. The circular design is larger while the mitered design is compact in size. The design developed has been simulated and the results have been compared to determine the performance between the two designs. The overall results prove that the Butler matrix designed with mitered bends performs better than the one with circular bends.